Eduard Hanslick Sämtliche Schriften, Historisch-kritische AusgabeBand I, 7: Aufsätze und Rezensionen 1864-1865 - Strauß, Dietmar (2011)
The present seventh volume of the new historical-critical complete edition of Eduard Hanslick's works contains texts of the years 1864 to 1865, which are for the most part contributions from the Vienna "Presse" and the "Neue Freie Presse", which Hanslick changed to when it was founded in 1864. In terms of content the texts offer a wide range. Apart from topical reviews there are basic essays on musical aesthetics, thoughts on the Italian opera in Vienna, historico-cultural accounts as well as basic reflections about the concert life in Vienna at that time. In particular Hanslick's research on the history of music in Vienna, which leads to "Geschichte des Concertwesens in Wien" published by Wilhelm Braumüller in 1869, shows in various single essays and a huge coherent series in "Oesterreichische Revue". Some articles were published shortly after in national music journals such as the "Niederrheinische Musik-Zeitung" or the Berlin music journal "Echo". Later Hanslick revised some of them for his well-known anthologies ("Die moderne Oper", "Aus dem Concertsaal. Geschichte des Concertwesens in Wien, II"). As before these texts were provided with lists of readings, which are printed subsequent to the respective article. The principles of publication did not change. Minor variations are: different spelling, change from spaced writing to normal distance of characters or vice versa, slight modifications of the wording, updating or additions. Major changes mainly consist in leaving out large parts of the text or rearranging text passages from different sources regarding particular subjects. The basic change in Hanslick's occupation as a critic that is his stronger attention to reviewing the performance, - as can be seen from the 1860s in particular - cannot be substantiated so well by his own editions, because he often left out parts related to the concert. From that point of view this edition not only provides a better overview of the Vienna concert life in these years than Hanslick's own edition but it also notes down in a much more precise way his changed approach to writing. Most of the texts, however, are completely unknown today. The essay in the comment part deals with Hanslick's change to the "Neue Freie Presse" and the importance of the latter for the circle of its authors. As before the notes characterize every single text briefly and analyse them according to their aesthetic relevance. The volume ends with a scientific apparatus (list of emended printing errors, list of abbreviations, bibliography and index of names).